Effect of Shade and Organic Manure on Growth and Yield of Patchouli [Pogostemon cablin (Blanco) Benth.] under Teak (Tectona grandis L. F.) Based Agroforestry System - Kumar, Devendra; Bijalwan, Arvind; Kalra, Alok; Dobriyal, Manmohan J. R. (Indian Forester, 2016)
The study on effect of shade and organic manure on growth and yield of Patchouli [Pogostemon cablin (Blanco) Benth.] under "Teak (Tectona grandis) based agroforestry system" was conducted. A field experiment of Patchouli was laid out separately under teak based agroforestry system and under open condition with seven treatments. The results revealed that dry herbage and oil yield of patchouli were highest under shade condition with treatment T2(100% vermicompost) compare to open condition at three harvest intervals. Beneficial effect of vermicompost in improving the soil environment which in turn encourages proliferous root growth resulting in better absorption of moisture, nutrients and thus producing higher biomass. Plant height was significantly influenced by open and shade cultivation. The chemical composition of the essential oils was evaluated quantitatively and qualitatively. Patchouli alcohol, major compound were also higher (42.3, 42.9%) under agroforestry system compared with open condition. The highest net return was noticed in T2 (`53, 013.00) followed by in T6(` 52, 396.00) and the BC Ratio was observed as 1:2.35 in T6 followed by T2 (1:2.32) under agroforestry. Final results revealed that Pogostemon cablin is a shade tolerant plant and its growth, yield and quality favoured under teak tree shade, thus can be explored as intercrop under agroforesty.